Green Synthesis of Dyes and Appliance on Silk by Using Metamordating Technique: Application of Dyes on Silk (Biological Sciences - PJSIR, 2021)
The main idea of extracting dyes from plant (natural) sources is to avoid the environmental pollution. Natural dye from plants has been given much interest in recent years due to the threat and harmful effects are used by synthetic dyes and environmental awareness created by researchers. The drawback of synthetic dyes is that they are not durable as they do not completely fix on all kind of fabric and remaining dyestuff drained into rivers, becoming the cause of water pollution as well as they cause diseases in human being like cancer and allergies. On the other hand, natural dyes are eco-friendly and find use in the colouring of textiles, drugs and cosmetics etc. Owing to their non-toxic effects, they are also even used for colouring various food products. Mordents are used in natural dyes which enhance the colour of dye and stick it on fabric. Due to lack of availability of precise technical knowledge on the extracting and dyeing technique, it has not commercially succeeded like the synthetic dyes. Hence, the present study was planned to isolate eco-friendly dyes from the bark of the plants (Ziziphus jujube Mill., Albizialebbeck L., Cordia dichotoma G Forst., Ficus benghalensis L. and Cassia fistula L.) and the roots of Ficus benghalensis L. Later on the dyes were applied on silk fabric by using metamordating technique. Then fastness properties like rubbing, heating, washing and sunlight were evaluated by using gray scale. F. benghalensis showed excellent fastness properties. Z. jujube showed series of colour variations on silk. Therefore, the bark and root of these plants can be successfully used for dyeing of silk. Natural dyes worldwide should be increased to prevent us from pollution and other harmful effects.